Mobilizaç\~ao social e deliberaç\~ao participativa na formaç\~ao da agenda governamental: Uma análise processual das conferências nacionais de economia solidária - Sandro Pereira Silva; Gabriela Cavalcanti Cunha; Regilane Fernandes da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper analyzes the relationship between social mobilization (of public and private actors) and the agenda of official participatory institutions in the field of solidarity economy. More specifically, it was sought to analyze, through participatory observation and documentary analysis, how this relationship occurred during the process of social-state interface promoted by the national conferences, especially the 3rd Conaes, which occurred in 2014 and triggered the elaboration of the National Plan of Solidarity Economy. In the end, it can be said that the conference process was appropriate for the part of the civil society involved in its theme as a link between its traditional mobilization repertoires and the opening of an official channel of contact with a representation of the public power.
Keywords: H19; 330; social participation; public policies; solidarity economy; national conferences; governmental agenda